The medical management of inflammatory bowel disease in primary care: the north bristol experience. (13th March 2011) - Arthurs, E A; Gholkar, B; Burley, K; Williams, L; Lockett, M
Abstract : Introduction: Evidence suggests that Aminosalicylates (5-ASA) have a chemopreventative effect in reducing rates of CRC in patients with colitis.1 It is recommended that patients should be maintained on a dose of 1.2 g/day.2 Immunomodulators are recommended for steroid refractory disease, but can cause myelosuppression, hence regular blood monitoring is advised.3 The aims are to assess whether patients with colitis in primary care are receiving appropriate chemoprevention with 5-ASAs; to determine whether patients on immunomodulators and biologicals are appropriately monitored and to identify patients on long-term steroids. Methods: Four GP practices were audited. Patients with IBD were identified from primary care computerised records and verified by paper notes. Data regarding diagnosis, date of symptom onset, disease extent and medication was collected and analysed. Individualised recommendations were made and a detailed report was given to each practice. Results: 214 patients with IBD were identified from 37 054 patients. 81 (37.9%) patients were taking 5ASA within this group. 96 (44.9%) patients had a diagnosis of colitis; 51 (53.1%) were taking 5-ASA; 42 (19.6%) had unknown extent of disease, and of these 7 (16.7%) were taking a 5-ASA. There was data from two practices regarding dosage and reasons for not taking recommended 5-ASA. Of 24 patients taking 5-ASA for colonic disease, 23 (95.8%) were taking more than or equal to 1.2 g/day. Most common reasons for not taking a 5-ASA were inactive disease/asymptomatic (11; 61.1%), unclear records (4; 22.2%), side effects (1; 5.6%), poor compliance (1; 5.6%), patient choice (1; 5.6%). Of 214 patients, 33 (15.4%) were on immunomodulators, with 24 (72.7%) undergoing appropriate monitoring according to an agreed shared care protocol. 7 patients (21.1%) had blood monitoring 6 monthly; 2 (6.1%) were not undergoing any monitoring. The reasons for lack of monitoring were unclear from records. There were 5 patients (2.3%) on biologicals, and no patients on long term oral steroids for > 3 months for colitis. All patients on immunomodulators and biologicals were under secondary care follow-up. Conclusion: The use of 5-ASA for chemoprevention in our general practice cohort was suboptimal. The majority of patients with IBD in primary care receiving immunosuppression were receiving appropriate monitoring and secondary care follow-up according to local agreements. There were no patients on long term oral steroids.